The Enemy within: Innate Surveillance-Mediated Cell Death, the Common Mechanism of Neurodegenerative Disease - Richards, Robert I.; Robertson, Sarah A.; O'Keefe, Louise V.; Fornarino, Dani; Scott, Andrew; Lardelli, Michael; Baune, Bernhard T. (Frontiers in Neuroscience, 2016)
Neurodegenerative diseases comprise an array of progressive neurological disorders all characterized by the selective death of neurons in the central nervous system. Although rare (familial) and common (sporadic) forms can occur for the same disease, it is unclear whether this reflects several distinct pathogenic pathways or the convergence of different causes into a common form of nerve cell death. Remarkably, neurodegenerative diseases are increasingly found to be accompanied by activation of the innate immune surveillance system normally associated with pathogen recognition and response. Innate surveillance is the cell’s quality control system for the purpose of detecting such danger signals and responding in an appropriate manner. Innate surveillance is an ‘intelligent system’, in that the manner of response is relevant to the magnitude and duration of the threat. If possible, the threat is dealt with within the cell in which it is detected, by degrading the danger signal(s) and restoring homeostasis. If this is not successful then an inflammatory response is instigated that is aimed at restricting the spread of the threat by elevating degradative pathways, sensitizing neighboring cells, and recruiting specialized cell types to the site. If the danger signal persists, then the ultimate response can include not only the programmed cell death of the original cell, but the contents of this dead cell can also bring about the death of adjacent sensitized cells. These responses are clearly aimed at destroying the ability of the detected pathogen to propagate and spread. Innate surveillance comprises intracellular, extracellular, non-cell autonomous and systemic processes. Recent studies have revealed how multiple steps in these processes involve proteins that, through their mutation, have been linked to many familial forms of neurodegenerative disease. This suggests that individuals harboring these mutations may have an amplified response to innate-mediated damage in neural tissues, and renders innate surveillance mediated cell death a plausible common pathogenic pathway responsible for neurodegenerative diseases, in both familial and sporadic forms. Here we have assembled evidence in favor of the hypothesis that neurodegenerative disease is the cumulative result of chronic activation of the innate surveillance pathway in a progressively expanding cascade.